The Passage of Nature - Emmet, Dorothy. author. aut Link
XI, 137 p.
Keywords: The concept of process is often used but seldom discussed. In this book the author looks at how a process differs from a series of events, facts or even just things changing. She claims causation is best seen in terms of processes and subsequently examines various aspects of this subject.